Using Rasch Model to Detect Differential Person Functioning and Cheating Behavior in Natural Sciences Learning Achievement Test - Susongko, Purwo; Kusuma, Mobinta; Widiatmo, Heru (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2019)
The existence of abberant response showed the inaccuracy of measurement which, in turn, threatens the test validity. This study aims at: (1) Discovering the proportion of students who were having Differential Person Functioning (DPF) in final term assessment test of natural sciences course for 8th grade in odd semester of academic year 2016/2017 in Tegal Regency, Indonesia; (2) Identifying the students suspected of cheating during the final term assessment test of natural sciences course for 8th grade in odd semester of academic year 2016/2017 in Tegal Regency, Indonesia. This research involved 1011 student responses to final term assessment test of natural sciences course for 8th grade in odd semester of academic year 2016/2017 in Tegal Regency, Indonesia. The data were taken from four junior high schools; SMPN I Dukuhturi, SMPN I Suradadi, SMPN 2 Slawi and SMPN 2 Dukuhwaru. The scoring was done using Rasch model and the person fit index used Sijtsma’s Ht person fit statistic (Ht). The result showed: (1) 14% of the students attending final term assessment of natural sciences course for 8th grade in the odd semester of academic year 2016/2017 in Tegal Regency, Indonesia were detected of having DPF. From the four junior high schools involved in the research, three junior high schools have a proportion of students having DPF at a range from 9.6% to 23%, and only 1.1% of the other one’s students were having DPF; (2) Nine pairs of students were suspected of cheating during the final term assessment of natural sciences course for 8th grade in the odd semester of academic year 2016/2017 in Tegal Regency, Indonesia.